The Influence of the Principal's Leadership Style, Work Motivation and Work Discipline on the Performance of MTS Negeri 2 Lamongan Teachers - Alviani; Sihab Ridwan (Formosa Journal of Applied Sciences, 2022)
This study aims to determine the influence of the principal's leadership style, work motivation and discipline partially or simultaneously on the teacher's performance at MTs Negeri 2 Lamongan. The design of this study used the ex post facto research method. The data used is quantitative data. The analytical method used is multiple linear regression test, data quality test, and classical assumption test. The analytical tool used in this study is SPSS 26. The results of this study indicate that the principal's leadership style partially has a significant effect on teacher performance at MTs Negeri 2 Lamongan, but work motivation and work discipline have no significant effect. And simultaneously the principal's leadership style, work motivation and work discipline have a significant effect on the teacher's performance at MTs Negeri 2 Lamongan.